When work–family guilt becomes a women's issue: Internalized gender stereotypes predict high guilt in working mothers but low guilt in working fathers - Aarntzen, Lianne; Derks, Belle; van Steenbergen, Elianne; van der Lippe, Tanja (British Journal of Social Psychology, 2023)
Les stéréotypes de genre prescrivent aux mères, mais pas aux pères, de donner la priorité à leur famille plutôt qu’à leur travail. Par conséquent, l’intériorisation des stéréotypes de genre peut prédire une culpabilité plus élevée chez les mères que chez les pères dans des situations où ils privilégient leur travail plutôt que leur famille. L’étude 1 (135 mères et 116 pères) a en effet révélé que plus les stéréotypes de genre implicites des pères étaient forts (mesurés à l’aide d’une tâche d’association implicite genre-carrière), moins les pères se déclaraient coupables dans une situation fictive d’interférence du travail dans la famille. Bien que les mères aient en moyenne déclaré une culpabilité plus élevée que les pères, cet effet n’a pas été atténué par leurs stéréotypes de genre implicites. L’étude 2 (étude du journal quotidien auprès de 105 mères) a toutefois révélé des preuves de l’effet modérateur des stéréotypes de genre implicites sur la culpabilité des mères qui travaillent. Plus les stéréotypes de genre implicites des mères étaient forts, plus elles déclaraient avoir des conflits entre le travail et la famille et de la culpabilité les jours où elles travaillaient de longues heures. Ces résultats montrent que les stéréotypes de genre implicites façonnent la façon dont les parents perçoivent leurs choix travail-famille.
Keywords: 2000 à aujourd'hui; 2020-2029; care; charge mentale; conciliation famille-travail; culpabilité; discipline; europe; famille; maternité; pays-bas; projet charge mentale; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; émotions

La charge mentale et l'anxiété qui en découle - Spill the Tea (2023)
Aujourd’hui, on jase avec vous de la charge mentale et de tout se qui en découle. Ne nous faisons pas de cachette, le rôle de maman apporte une énorme charge mentale pour la plupart d’entre nous et nous avions envie de s’ouvrir sur le sujet. On espère que l’épisode saura vous apaiser et vous montrer que vous n’êtes pas seules.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; anxiété; charge mentale; conciliation famille-travail; famille; maternité; projet charge mentale; périodes historiques; québec; régions géographiques; santé; santé mentale des mères; thématiques; travail

“The workload is staggering”: Changing working conditions of stay-at-home mothers under COVID-19 lockdowns - Aslam, Awish; Adams, Tracey L. (Gender, Work and Organization, 2022)
The COVID-19 pandemic has drawn attention to the home as a work environment, but the focus has centered on the experiences of paid workers. Stay-at-home mothers (SAHMs), for whom the home was already a workplace, have received little attention. This article explores how pandemic-induced lockdowns impacted SAHMs' working conditions and their experiences of childrearing. Combining a Marxist-feminist conceptualization of domestic labor with a labor process framework, we performed a qualitative content analysis of vignettes SAHMs shared about their day-to-day domestic labor in an online mothering community. Our findings show that, under lockdown conditions, the primacy given to partners' paid work combined with children's increased demands for care and attention reduced SAHMs work autonomy and exacerbated gender inequalities in the home. Combining labor process theory with literature on motherwork illuminates the home as a gendered work environment and enhances understanding of how changing conditions of domestic labor can intensify gender inequalities (and workers' awareness of them) that typically remain “hidden in the household.”. © 2022 John Wiley & Sons Ltd.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; discipline; féminisme marxiste; féminisme matérialiste; inégalités; maternité; mères au foyer; projet charge mentale; périodes historiques; ressource en ligne; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail de reproduction

"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

Les femmes dans l’industrie musicale canadienne francophone - Bissonnette, Joëlle (Fondation Musicaction, 2022)
Ce rapport présente les résultats d’une étude menée depuis 2020 afin de mettre en lumière la place des femmes dans le secteur. Cette étude a été dirigée par Joëlle Bissonnette, pour et avec la collaboration de la Fondation Musicaction et grâce à l’appui du Gouvernement du Canada. Au terme de cette vaste étude, plus de 600 témoignages ont pu être recueillis et analysés. Ceux-ci ont permis de relever les défis particuliers rencontrés par les femmes dans le secteur et de faire ressortir des pistes de solution pouvant favoriser leur épanouissement professionnel. Les pistes de solution dégagées reflètent les besoins exprimés par les participantes, des femmes de tous les corps de métier, et les recommandations qu’elles ont formulées pour répondre aux défis soulevés. En somme, ces résultats peuvent servir de coffre à outils pour inspirer toutes les parties prenantes du secteur, selon leur champ d’action respectif, et ainsi stimuler une meilleure inclusion des femmes dans l’industrie canadienne francophone.
https://archipel.uqam.ca/15362/1/musicaction_rapport_versionlongue_vf.pdf
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; canada; division sexuelle du travail; femmes* artistes; harcèlement psychologique; harcèlement sexuel; maternité; périodes historiques; représentations; ressource en ligne; régions géographiques; santé; santé des femmes*; sexisme; systèmes d'oppressions; thématiques; travail; violences

La recherche de reconnaissance des parents LGBTQ+ : une approche féministe illustrée - Lambert, Stéphanie (Université du Québec à Montréal, 2022)
Depuis une perspective située, cette investigation en travail social documente la négociation de modifications à apporter aux représentations culturelles des familles LGBTQ+ circulant dans l’espace public québécois, par quatre parents LGBTQ+ et l’étudiante-chercheure. L’exercice, sous forme de focus group, avait pour but de favoriser l’échange et de créer de nouvelles images pouvant leur sembler plus justes en fonction de leurs propres expériences de parentalité. La démarche visait également à répondre à la question suivante : quelle forme de reconnaissance est recherchée par les parents LGBTQ+ montréalais, et de quelle manière? Elle s’inscrit dans les théories de la justice, où la reconnaissance est un élément clé à la pleine participation des individus et des collectivités dans leur société. Une analyse du contenu thématique, émergeant des réflexions des participants-es au focus group, recense trois statuts subordonnés (selon Nancy Fraser) auxquels les parents LGBTQ+ font face. Il s’agit de statuts liés au projet national québécois, au sexisme et au genrisme, et à la famille naturelle. De plus, l’attention portée aux interactions des parents permet d’observer le souci à autrui prenant place au sein de leurs échanges, à la lumière des quatre phases du care de Tronto et des perspectives de Ricoeur sur la reconnaissance. La quête de reconnaissance est donc exposée non seulement comme une lutte personnelle, mais aussi telle une démarche démontrant l’attention à soi et à l’autre. Cette observation va à l’encontre de certaines représentations culturelles rencontrées où les parents LGBTQ+ sembleraient davantage préoccupés par leurs propres désirs, besoins et droits, que ceux de leur entourage, incluant leurs enfants et leurs pairs marginalisés. Cette recherche qualitative à caractère exploratoire a recours à l’illustration pour interpeller le public ciblé, éliciter les données, développer l’analyse, présenter les matériaux et uniformiser le travail. Les limites observées sont liées au petit échantillonnage comme au caractère artificiel (initié par l’étudiante) du processus de recherche de reconnaissance en groupe. Des recherches ultérieures auprès d’enfants et d’adolescents de parents LGBTQ+, ou encore auprès d’autres groupes minoritaires pourraient mettre en corrélation et solidifier les données mises de l’avant. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : reconnaissance, parentalité, homoparentalité, transparentalité, pluriparentalité, LGBTQ+, queer, care, justice, Fraser, Tronto, Ricoeur, féminisme, bande dessinée, illustration, représentations culturelles, famille, travail social.
https://uqam-bib.on.worldcat.org/oclc/1368201405
Keywords: 2000 à aujourd'hui; 2020-2029; LGBTQIA2+; amériques; approches et analyses; bande-dessinée; biblioFem*; care; discipline; identités LGBTQIA2+; justice sociale; maternité; montréal; mémoires/thèses; parentalité; périodes historiques; queer; québec; représentations; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social; étude qualitative

Gendered impacts of the COVID-19 pandemic: A mixed-method study of teacher stress and work-life balance - Leo, Aaron; Holdsworth, Elizabeth A.; Wilcox, Kristen C.; Khan, Maria I.; Mola Ávila, José Antonio; Tobin, Jessie (Community, Work and Family, 2022)
There is a growing concern that the COVID-19 pandemic has had disproportionate impacts on women, especially those with children. Female educators, and, in particular, those with childcare responsibilities, have also reported higher levels of stress and work-life challenges as compared to their male counterparts. It is unclear exactly which factors are behind these disparities. However, while some have pointed to the gendered division of domestic labor as the main contributor, other pandemic-related and work-related stressors may be involved in female educators’ increased stress levels and work-life balance challenges. To address this question, this mixed-methods research draws on survey data gathered from 752 educators across New York State. Findings demonstrate that women reported higher levels of stress and work-life balance challenges than their male counterparts. While quantitative analyses indicated that gender disparities in work-life balance challenges were related to the higher stress women experienced from work and COVID-19 rather than childcare responsibilities, qualitative analyses of open-ended survey responses revealed that childcare duties were nonetheless an important factor impacting work-life balance challenges for both men and women. This article has significant implications for the teaching profession and adds broader insights into the gendered effects of the pandemic. © 2022 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; covid-19; division sexuelle du travail; inégalités; maternité; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; santé au travail; systèmes d'oppressions; thématiques; travail; états-unis

The entrenchment of the ideal worker norm during the COVID-19 pandemic: Evidence from working mothers in the United States - Zanhour, Mona; Sumpter, Dana (Gender, Work and Organization, 2022)
We study shifts in the ideal worker culture as experienced by working mothers across organizations in the United States during the COVID-19 pandemic. Experiences of 53 interviewees who attended to increased responsibilities across both work and family domains revealed an entrenchment of the ideal worker culture across nearly all organizations and professions. This manifested in three levels: as (1) a reinforced ideal worker culture in the workplace through work intensification, increased competitiveness, and surface-level support; (2) the reinforcing of organizations' ideal worker norms at home, with gendered division of space and labor; and (3) experienced internalized ideal worker norms in the expectations working mothers maintained for themselves. These findings offer insight into the lives of working mothers during the COVID-19 pandemic and the challenges which have pushed many mothers to reduce work hours or leave the workforce. Highlighting the intricate nature of the entrenchment of the ideal worker culture informs implications for theory of gendered organizations and for organizational practice. © 2022 John Wiley & Sons Ltd.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; conciliation famille-travail; culpabilité des mères; famille; maternité; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail; travail des mères; états-unis

Women and burnout in the context of a pandemic - Aldossari, Maryam; Chaudhry, Sara (Gender, Work & Organization, 2021)
This article presents the lived narrative of a female academic with children working in a British university and trying to cope with a completely new way of work and life in the context of the pandemic. The overall aim of the article is to offer a gendered account of burnout—specifically how women may be experiencing burnout at multiple levels, and the efficacy of their subsequent coping strategies. The narrative provides insights into how a range of coping mechanisms such as disengagement, denial, and energy conservation are deployed to deal with the increased responsibilities at work and home as a result of the pandemic. Existing research has viewed burnout as gender neutral, leaving a gap in the literature on the significant differences in both men's and women's experience of burnout as well as their coping behaviors.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; burn-out; charge mentale; division sexuelle du travail; double journée de travail; europe; inégalités; maternité; privilèges; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; santé; systèmes d'oppressions; thématiques; travail

Producing the patchwork: The hidden work of mothers in organizing child care. - Breitkreuz, Rhonda; Colen, Kerryn; Horne, Rebecca (Journal of Family Studies, 2021)
This article aims to explore how child care is organized in families, documenting how mothers produce their individual child care solution, or “patchwork”, within the context of Canada’s underfunded and fragmented child care system. In a sample of 109 mothers from Alberta, Canada, where child care is conceptualized as primarily a private family responsibility, we use an ecocultural theoretical framework and a gender lens to 1) identify the constraints that influenced what kinds of child care mothers used, 2) explore the organization of day-to-day child care arrangements, and 3) explicate the accommodations and flexibility required to sustain the family routine. We show that in addition to previously recognized categories of child care—formal, informal, and mixed—families also used multiple informal and parent-plus (i.e., parental plus non-parental) child care. The procurement and management of child care—particularly when multiple care providers were involved—was gendered, often invisible, and required substantial accommodations and flexibility by mothers. We propose a day-care plus policy model of child care, where formal arrangements are supplemented as required. This policy model could help families avoid the complex scenarios we conceptualize as chaotic flexibility and assist families in achieving sustainable flexibility in the organization of care. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; canada; charge mentale; charge mentale des femmes; maternité; projet charge mentale; périodes historiques; régions géographiques; soins aux enfants; stratégie alternative de garde d'enfants; système de garderie; thématiques; travail; travail de reproduction